Prevalence of anti-BK polyomavirus IgG in A Sample of Iraqi renal transplant recipients - Hammoodi Abed, Ghufran; Mahdi alsaeed, Wisam; Rasul Hussein, Mustafa; Baqer Al-Obaidi, Asmaa; Sattar Abood, Ahmed; A.H. Al-Dabagh, Mohammad (Diyala Journal of Medicine, 2022)
Background: BK virus, a human polyomavirus, causes nephropathy and allograft loss in renal transplant recipients. Although it was discovered in 1971, understanding of the humoral immune response to BKV is limited. Objective: To serological detection and level estimation of anti-BK-IgG in renal-transplanted recipients and healthy blood donors as control. Patients and Methods: Serum samples were collected from 106 renal transplant recipient patients and 100 healthy blood donors as control groups, and were analyzed for anti-BK IgG antibodies by using quantitative and qualitative Human BK Virus IgG (BK-IgG) ELISA kit for detection and estimation positivity of BK_IgG and titration. Results: Out of 206 subjects, 114(55.3%) have a positive result for BK-IgG. seropositivity was detected in 54(50.9%) of 106 RTR patients and 60 (60.0%) in the 100 control group, so there was no significant difference between seropositivity of BKV IgG antibody among the studied groups, p =0.191. Conclusion: The highly significant differences between seropositivity of BK-IgG with high levels of serum creatinine.